Teacher Professionalism In The Teaching And Learning Process To Improve The Quality Of Student Learning At MTs An-Nur Pamekasan - Hosna, Rofiatul; Siti Taskiyatul Fikriyah; Amalia (Tebuireng: Journal of Islamic Studies and Society, 2024)
This study examines the learning process carried out by teachers that has an impact on their professionalism in student learning motivation at MTs An-Nur Pamekasan. The research taken for the smoothness and quality of this work is qualitative research. By utilizing interviews to collect the necessary data, observation to strengthen the information that was touched, and documentation to support the complete and strong data that the researcher has found. Research findings show that the role of teacher professionalism in the teaching and learning process greatly influences students' learning motivation so that the impact that will be affected is their learning outcomes.